2020
DOI: 10.3390/agronomy10101606
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Nitrogen Application Increases Soil Water Extraction by Changing in-Season Maize Root Morphology and Distribution in Rainfed Farmland

Abstract: The proper promotion of a deep root system is important for maize cultivation to improve water use efficiency in the arid and semi-arid Loess Plateau. Here, a field experiment was conducted to assess the effect of combined controlled release urea and normal urea on root growth and water extraction of maize in dryland fields. Maize in the combined controlled release urea and normal urea treatment had greater root systems compared to those in the normal urea treatment and no N application treatment. Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…The results suggested that the combination of an optimal fertilization rate and CRU-N can further improve net benefits by increasing profits and decreasing labor costs. The synchronization of N supply and crop absorption by controlling N release can maximize NUE [40,45] .…”
Section: Effects Of Different Nitrogen Fertilization On Maize 341 Lea...mentioning
confidence: 99%
“…The results suggested that the combination of an optimal fertilization rate and CRU-N can further improve net benefits by increasing profits and decreasing labor costs. The synchronization of N supply and crop absorption by controlling N release can maximize NUE [40,45] .…”
Section: Effects Of Different Nitrogen Fertilization On Maize 341 Lea...mentioning
confidence: 99%
“…Optimum N application enhanced biomass production that also enhanced the requirement for roots to absorb maximum water from the deeper soil layer. The combination of slow release and monotypic N fertilizers enhanced the maize root length and weight densities at dent stage in the deeper soil layers 44 . Hu et al 45 found that controlled release urea increased deeper root growth, and deeper soils has more soil water storage making it easy for plants to uptake water to fulfill its requirement at maize dent growth phase.…”
Section: Discussionmentioning
confidence: 95%
“…The controlled-or slow-release nitrogen fertilizers have another advantage; they promote healthy root growth [74,75]. As the nitrogen is released slowly, it allows the roots to grow deeper into the soil in search of nutrients.…”
Section: The Pros and Cons Of Srn And Crn Applicationmentioning
confidence: 99%